Dental anomalies And Facial Profile abnormality Of The Non-Syndromic Cleft Lip and Palate Children In Kelantan. - Abd. Rahman, Normastura; Abdulah, Nizam; Samsudin, Abdul Rani; Sadiq, Lin Naing @ Mohd Ayub (2004)

(untitled)
Cleft lip and palate (CLP) has become a major public health problem affecting one in every 500 1000 births worldwide (1).